2009
DOI: 10.1073/pnas.0908366106
|View full text |Cite
|
Sign up to set email alerts
|

Missing and spurious interactions and the reconstruction of complex networks

Abstract: Network analysis is currently used in a myriad of contexts, from identifying potential drug targets to predicting the spread of epidemics and designing vaccination strategies and from finding friends to uncovering criminal activity. Despite the promise of the network approach, the reliability of network data is a source of great concern in all fields where complex networks are studied. Here, we present a general mathematical and computational framework to deal with the problem of data reliability in complex ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
597
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 690 publications
(600 citation statements)
references
References 34 publications
2
597
0
1
Order By: Relevance
“…Notice that, the number of different partitions of N elements grows faster than any finite power of N, and thus even for a small network, to sum over all partitions is not possible in practice. The Metropolis algorithm [94] can be applied to estimate the link reliability [18]. Even though, the whole process is very time consuming and this method can only manage networks with up to a few thousands of nodes.…”
Section: Stochastic Block Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Notice that, the number of different partitions of N elements grows faster than any finite power of N, and thus even for a small network, to sum over all partitions is not possible in practice. The Metropolis algorithm [94] can be applied to estimate the link reliability [18]. Even though, the whole process is very time consuming and this method can only manage networks with up to a few thousands of nodes.…”
Section: Stochastic Block Modelmentioning
confidence: 99%
“…The stochastic block model can capture the community structure [22], role-to-role connections [88] and maybe other factors for the establishing of connections, especially when the group membership plays the considerable roles in determining how nodes interact with each other, which usually could not be well described by the simple assortativity coefficient [89,90] or the degree-degree correlations Given a partition M where each node belongs to one group and the connecting probability for two nodes respectively in groups α and β is denoted by Q αβ (Q αα represents the probability that two nodes within group α are connected), then the likelihood of the observed network structure is [18]:…”
Section: Stochastic Block Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Liang et al [42] found that scientists had referencing misbehavior and behavior of self-copying of references. Therefore, the tolerance of the algorithm against spurious links is an appropriate metric [43]. In this letter, we measure the performance of effectiveness and robustness among the CAM method, Shen's method and (T C) method in rankings by Kendall's Tau, τ and the Jaccard index S when citation links are added or rewired randomly, which is very common in real citation networks [31,44].…”
Section: Versatility Of the Cam Methods In Empirical Networkmentioning
confidence: 99%